Transcriptional activation and chromatin remodeling of the HIV-1 promoter in response to histone acetylation. - Van Lint, C (1996)
After integration in the host cell genome, the HIV-1 provirus is packaged into chromatin. A specific chromatin disruption occurs in the HIV-1 promoter during transcriptional activation in response to TNF-alpha, suggesting that chromatin plays a repressive role in HIV-1 transcription and that chromatin modification(s) might result in transcriptional activation. We have treated several cell lines latently infected with HIV-1 with two new specific inhibitors of histone deacetylase, trapoxin (TPX) and trichostatin A (TSA), to cause a global hyperacetylation of cellular histones. Treatment with both drugs results in the transcriptional activation of the HIV-1 promoter and in a marked increase in virus production. Dose-response curves and kinetic analysis show a close correlation between the level of histone acetylation and HIV-1 gene expression. In contrast, both TPX and TSA have little or no effect on HIV-1 promoter activity following transient transfection of an HIV-1 promoter-reporter plasmid. Activation of HIV-1 transcription by TSA and TPX treatment occurs in the absence of NF-kappa B induction. Chromatin analysis of the HIV-1 genome shows that a single nucleosome (nuc-1) located at the transcription start and known to be disrupted following TNF-alpha treatment, is also disrupted following TPX or TSA treatment. This disruption is independent of transcription as it is resistant to alpha-amanitin. These observations further support the crucial role played by nuc-1 in the suppression of HIV-1 transcription during latency and demonstrate that transcriptional activation of HIV-1 can proceed through a chromatin modification.